(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The results of a study of the structures, compositions and physicochemical properties of gossypol resin and other ingredients are presented. The possibility of using them in the development of composite chemical preparations for treating cotton seeds has been shown.